Pengaruh Kualitas Produk, Promosi Dan Lokasi Strategis Terhadap Keputusan Nasabah Menabung Di Bank BCA Pondok Ungu Bekasi - Dimas Anugrah; Andrian; Haryudi Anas (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The Influence of Product Quality, Promotion and Strategic Location on Customers' Decisions to Save at Bank BCA Pondok Ungu Bekasi. his research aims to empirically test the influence of product quality, promotion and strategic location on customers' decisions to save at Bank BCA Pondok Ungu Bekas. The sample for this research is BCA Pondok Ungu Bekasi City customers who have an interest in saving at BCA Bank. The sample was carried out using a non-probability sampling method, namely purposive sampling. Data collection was carried out using a questionnaire distributed via Google Form to 92 respondents. The analysis in this research uses Multiple Linear Regression Analysis, with t test hypothesis testing. The results of this research show that in the partial t test Product Quality has a significant effect on the decision to save, Promotion has a significant positive effect on the decision to save, and Strategic location has a significant positive effect on the decision to save. The results of the f test show that the variables Product Quality, Promotion and Strategic Location simultaneously influence the decision to save at BCA Bank for BCA Pondok Ungu Bank customers, Bekasi City.